A study of crack‐fiber interaction in fiber‐reinforced composites using optical caustic method. Issue 4 (23rd June 2014) - Tang, Can
Abstract : In this article, the matrix crack‐fiber buddle interaction in fiber‐reinforced composites is investigated analytically and experimentally. First, the influence of the fiber buddle on the matrix crack is analyzed based on Eshelby equivalent inclusion method. Then the effect of dimensions and material properties of the fiber buddle on the stress intensity factor (SIF) of the matrix crack is studied numerically. Finally, a low velocity impact experiment of fiber‐reinforced composites with a matrix crack is conducted using optical caustic method to verify the analytical and numerical results. POLYM. ENG. SCI., 55:852–857, 2015. © 2014 Society of Plastics Engineers